Green Chemistry Teaching Materials Training with Coastal Area Potential to Improve Chemistry Literacy and SDGs Understanding of Chemistry Teachers - Inelda Yulita; Muhamad Al Rasyid; Steva Dara Putri; Fadhliyah Idris (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
Chemistry learning should not only emphasize theoretical concepts but also connect learning with real environmental problems and sustainability issues. However, most teachers still use generic teaching materials that are less relevant to local potential and contextual learning needs. This community service activity aimed to improve teachers’ understanding of green chemistry, contextual learning, and Sustainable Development Goal (SDG 4) through training on developing green chemistry teaching materials based on coastal local potential. The activity involved members of MGMP Kimia Tanjungpinang and applied a Participatory Action Research (PAR) approach combined with project-based activities. The implementation stages included preparation, training, mentoring, and evaluation. Data were collected using competency assessment sheets, observation sheets, product assessment rubrics, and participant response questionnaires administered before and after the activity. The results showed measurable improvements in teachers’ competencies. Teachers’ understanding of green chemistry concepts increased from 68.75% to 100%, the ability to develop contextual teaching materials increased from 68.75% to 100%, competence in integrating coastal local potential into chemistry learning increased from 56.25% to 87.5%, chemical literacy in learning increased from 56.25% to 87.5%, and understanding of the relationship between chemistry learning and SDG 4 increased from 50% to 87.5%. Participants also successfully developed green chemistry teaching materials based on local coastal potential that were ready for classroom use. The activity contributed to SDG 4 by strengthening teachers’ professional competencies and improving the quality of contextual chemistry learning materials. These findings indicate that contextual green chemistry training effectively enhances teachers’ chemical literacy, understanding of SDG 4, and competency in developing meaningful and contextual teaching materials.